2012
DOI: 10.1097/meg.0b013e32834f6baa
|View full text |Cite
|
Sign up to set email alerts
|

Reflux and sex

Abstract: Gastroesophageal reflux (GER) affects ∼10-20% of American adults. Although symptoms are equally common in men and women, we hypothesized that sex influences diagnostic and therapeutic approaches in patients with GER. PubMed database between 1997 and October 2011 was searched for English language studies describing symptoms, consultative visits, endoscopic findings, use and results of ambulatory pH study, and surgical therapy for GER. Using data from Nationwide Inpatient Sample, Healthcare Cost and Utilization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 297 publications
0
7
1
Order By: Relevance
“…The percentage of patients with severe esophagitis of grades C and D was 14.7%, which was higher than the percentages in other studies performed in Japan, but did not differ significantly from those in previous Japanese studies focusing on elderly females [3,4,5,6,7,43,44,45,46], although the prevalence of severe esophagitis in females was the same as that in males in Western countries [47]. The present study further indicated that the risk factors for an increase in severe reflux esophagitis of grades C and D in aged females were lumbar kyphosis, hiatus hernia, negative H. pylori infection status, short height and high age, which were compatible with previous reports [3,4,5,8,9].…”
Section: Discussioncontrasting
confidence: 46%
“…The percentage of patients with severe esophagitis of grades C and D was 14.7%, which was higher than the percentages in other studies performed in Japan, but did not differ significantly from those in previous Japanese studies focusing on elderly females [3,4,5,6,7,43,44,45,46], although the prevalence of severe esophagitis in females was the same as that in males in Western countries [47]. The present study further indicated that the risk factors for an increase in severe reflux esophagitis of grades C and D in aged females were lumbar kyphosis, hiatus hernia, negative H. pylori infection status, short height and high age, which were compatible with previous reports [3,4,5,8,9].…”
Section: Discussioncontrasting
confidence: 46%
“…The current evidence on the association between gender and GERD symptoms is mixed, but the majority of studies have not shown any association [65]. However, in most studies with endoscopy, non-erosive GERD have been more common in women [66], whereas erosive esophagitis have been more common in men [65][67].…”
Section: Discussionmentioning
confidence: 99%
“…However, in most studies with endoscopy, non-erosive GERD have been more common in women [66], whereas erosive esophagitis have been more common in men [65][67]. The reported prevalence of symptoms and histological damage related to GERD varies across ethnic/racial groups [68], [69].…”
Section: Discussionmentioning
confidence: 99%
“…Second, only about one-third of the MS patients with dysphagia complained of esophageal symptoms such as heartburn or odynophagia. Lastly, reflux symptoms or a diagnosis of GERD, the most common cause of esophageal dysphagia, were reported by MS patients at rates similar to those seen in the general population [28]. …”
Section: Discussionmentioning
confidence: 99%